2019
DOI: 10.1177/0049124119852369
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Peer Influence Estimates from SIENA Stochastic Actor–based Models and from Conventional Regression Approaches

Abstract: The current study compares estimates of peer influence from an analytic approach that explicitly address network processes with those from traditional approaches that do not. Using longitudinal network data from the PROmoting School–community–university Partnerships to Enhance Resilience peers project, we obtain estimates of social influence on multiple outcomes from both conventional linear modeling approaches and the stochastic actor–based modeling approach of the simulation investigation for empirical netwo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 43 publications
2
19
0
Order By: Relevance
“… 12. For models comparing clustered standard errors and more computationally intensive approaches to relational processes and social influence, see Lindgren (2010) and Ragan and colleagues (2019). These offer broad support for the robustness of models presented here. …”
supporting
confidence: 57%
“… 12. For models comparing clustered standard errors and more computationally intensive approaches to relational processes and social influence, see Lindgren (2010) and Ragan and colleagues (2019). These offer broad support for the robustness of models presented here. …”
supporting
confidence: 57%
“…A recent review by Advani and Malde (2018) and work by Carrell et al (2013) points out how not accounting for such heterogenous characteristics within groups may lead to biased estimates of peer effects in traditional models. Despite these challenges, there is recent work showing that traditional regression-based approaches to estimating peer influence can perform well relative to newer, less-restrictive analytic techniques that jointly model network dynamics and selection processes ( Ragan et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The model is also relatively inflexible as researchers can only use pre-defined network and behavioral terms. More importantly, although SAOM simultaneously models contagion and network-selection processes, it can still suffer from the aforementioned omitted variable bias problem, and contagion estimates from SAOMs are not more conservative relative to other conventional methods [45] . As Steglich et al pointed out, estimates from SAOMs are still biased when “non-observed variables co-determine the probabilities of change in network and/or behavior [40] .”…”
Section: Stochastic Actor-oriented Modelsmentioning
confidence: 99%